Mathematical model proposal and cost optimization in the creation of an emission reduction roadmap for an industrial enterprise in Turkey - Can, Deniz (Graduate School, 2023)
Global warming is showing its effect day by day. While countries approach combating the climate crisis from an environmental perspective, this tackling the climate crisis is reflected in the industry as a financial sanction. The best and most functional example of these financial sanctions is the emissions trading system. Turkey is one of the nations that is probably going to set up an Emissions Trading System (TR ETS). The Carbon Border Adjustment Mechanism (CBAM) accelerates this process. As a result of Turkey's struggle with the climate crisis, financial sanctions will be reflected on the industry as in other countries. Self-protection of companies against these financial sanctions (e.g. possible TR ETS) is through creating an individual emission reduction roadmap. Process integration is a preferred approach to use energy sources more efficiently and reduce environmental impacts. One of the types of process integration is pinch analysis. Carbon emission pinch analysis (CEPA) is frequently used type of pinch analysis in national energy planning by including emission constraints. In the CEPA methodology, an emission factor is determined for each energy source, while an emission limit is determined for each energy sink. In this study, a mathematical model has been proposed for enterprise-specific (micro scale) energy planning using CEPA methodology. Within the context of this study, a system-wide (enterprise-wide) emission constraint has been determined, and this emission constraint is the emission reduction target of the company. In this study, a mathematical model is proposed to be used in order to determine the green transformation roadmap that an industrial enterprise will implement in line with its emission reduction target. The objective function of the mathematical model is to maximize the net present value of the system by considering the environmental and financial effects. Seven different green transformation proposals are included in the mathematical model.
Türkiye'de bulunan bir endüstriyel işletme için emisyon azalttım yol haritasının oluşturulmasında matematiksel model önerisi ve maliyet optimizasyonu
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: Mathematical models; Matematiksel modeller; Emission reduction; Emisyon azaltımı